INTEGRATED DIAGNOSTIC APPROACHES TO VIRAL HEPATITIS B IN CONTEMPORARY CLINICAL PRACTICE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Viral hepatitis B remains one of the most pressing problems of modern clinical medicine due to its high prevalence, risk of chronicity, and the development of severe complications, including liver cirrhosis and hepatocellular carcinoma. This article reviews current approaches to the comprehensive diagnosis of viral hepatitis B, encompassing clinical, serological, molecular biological, and instrumental methods of investigation. Special attention is given to the identification of HBV infection markers (HBsAg, HBeAg, anti-HBc, anti-HBs), quantitative determination of hepatitis B virus DNA using polymerase chain reaction (PCR), as well as assessment of liver functional status based on biochemical parameters. The significance of a comprehensive diagnostic approach is demonstrated for early detection of the disease, determination of the stage and activity of the infectious process, monitoring the effectiveness of antiviral therapy, and predicting disease outcomes. The application of modern diagnostic technologies contributes to improved diagnostic accuracy and enhanced quality of medical care for patients with viral hepatitis B.